SITUAÇÃO VACINAL DAS CRIANÇAS DO ESTADO DE GOIÁS - Claci Fátima Weirich Rosso; Maria Alves Barbosa; Ruth Minamisava Faria; Lourdes Maria Silva Andraus (Universidade Federal de Goias, 1999)
The governament of Goiás settled a Support Program of Needy Families (PAFC), that assists nearly 160,000 families, which receive food monthly and other benefits. On this study we investigated the vaccination of children under 6 years old of the families registered in PAFC. The data were collected by the authors and for research assistants for this end, in the period of August to November of 1997. 1265 children's appraised cards were investigated, being 429 of the Goiânia city and 836 of other districts. 91,23% of all children were vaccinated according to the recommendations of Ministry of Health. We concluded that the offer of the food basket, conditioned to the exhibition of the child's card can have been contributing with the goals of the immunization program.